Effect of Relaxation Techniques and Education on Lowering Blood Pressure in Pregnant Women at Risk of Preeclampsia - Eny Indriyani (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Preeclampsia is a pregnancy complication that poses serious risks to both maternal and fetal health, characterized by a significant increase in blood pressure. In Indonesia, the prevalence of preeclampsia remains high, and delayed treatment can contribute to increased maternal and neonatal mortality. Unfortunately, many pregnant women at risk of preeclampsia do not receive optimal care, particularly in managing elevated blood pressure. Relaxation techniques and health education are considered effective non-pharmacological interventions to help reduce blood pressure and improve maternal health outcomes. This study aimed to analyze the effect of relaxation techniques and education on blood pressure reduction among pregnant women at risk of preeclampsia at RSIA Mutiara Bunda. A quasi-experimental design with a one-group pretest–posttest approach was employed. The sample consisted of 15 pregnant women at risk of preeclampsia, selected through purposive sampling. The interventions included relaxation techniques, such as deep breathing and guided visualization, as well as education on healthy lifestyle practices and stress management. Data were analyzed using a paired t-test. The results demonstrated a significant decrease in blood pressure following the intervention, with p-values < 0.05. These findings indicate that relaxation techniques combined with education are effective in lowering blood pressure among pregnant women at risk of preeclampsia. In conclusion, the implementation of relaxation techniques and educational interventions is essential in supporting preeclampsia prevention and management efforts.